Maisy Loves Trees : explore and learn! - Cousins, Lucy (Somerville, Mass. : Candlewick Press, 2024)
Maisy shares her knowledge of trees with loyal and new friends alike, in this celebration of a vital part of the natural world that features a gatefold of trees from around the globe.
Cover title.
On board pages with fold-out page.
new kids book 2024 spring.
Ages 01-03
Keywords: Maisy -- (Fictitious character from Cousins) -- Juvenile fiction; Board books; Mice -- Juvenile fiction; Trees -- Juvenile fiction; Board books